Comparative Quantum Chemical Examination of Lithiation/Delithiation Processes in Sin Nanoclusters and CmSin Nanocomposites - M. T. Kartel; V. S. Kuts; A. G. Grebenyuk; Yu. А. Tarasenko (Хімія, фізика та технологія поверхні)
A comparative quantum chemical (РМ3 method) examination has been carried out of lithiation/delithiation processes in Sin nanoclusters and СmSin nanocomposites. These processes in the nanocomposites (25 and ~30% С, respectively) have been shown to effect slightly on the volumes and structures of initial (СmSin), lithiated (Lik=0-52СmSin), and delithiated (Lik=52-0СmSin) silicon-carbon matrices Si/С. Electrodes from such materials should not undergo destructive effect of periodic deformations in charge/discharge cycles. On the contrary, at lesser carbon concentrations (С6Si13 nanocomposite, ~16% С) lithiation results in the 1.8 times hopping expansion of V(С6Si13), and delithiation – in the change in structure of initial silicon-carbon matrix Si/С. For Si/С electrodes with greater (more than 37%) carbon concentration (Сm>18Sin composites), lithiation results in a monotonous increase in the volume (1.3 times for С18Si13 and 1.5 times for С26Si13) whereas delithiatin leads to a considerable change in the initial structure of silicon-carbon matrix.